In vitro antimicrobial and antioxidant activities of Sambucus williamsii and Sambucus pendula - Kyoung-sun Seo; Kyeong Won Yun (International Journal of Secondary Metabolite)
The present study aimed to compare the in vitro antimicrobial and antioxidant activities of Sambucus williamsii and Sambucus pendula. The antimicrobial activity of the two plants was evaluated using the disc diffusion and minimal inhibition concentration (MIC) method against three Gram-positive bacteria (Bacillus cereus ATCC 11778, Bacillus subtilis ATCC 9327 and Listeria monocytogenes ATCC 15313), four Gram-negative bacteria (Escherichia coli ATCC 15489, Psendomonas aeruginosa ATCC 27853, Pseudomonas fluorescens KCCM 41443 and Salmonella typhimurium KCCM 11862) and one yeast (Saccharomyces cerevisiae IFO 1950). The tested ether and ethyl acetate fractions of ethanol extract from Sambucus williamsii showed significant antimicrobial activity against Bacillus cereus and Pseudomonas fluorescens; conversely, the ether fraction of Sambucus pendula leaf showed no clear zone formation against any tested bacteria. In general, the fractions of the two Sambucus species exhibited a lower MIC against tested Gram-negative bacteria than the tested Gram-positive bacteria. The antioxidant activity was evaluated by 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging assay. The results showed that the half inhibitory concentration (IC50) for the ethanol extract of Sambucus williamsii was the lower value, which means the greater antioxidant activity. On the other hand, the IC50 value of the hot water extract of Sambucus pendula was the lower value. The richness of the total polyphenol contents of the two Sambucus implies their potential as raw material sources for the pharmaceutical and cosmeceutical industries.